A new ultrasound‐guided surgical technique to fix acute tibial posterior cruciate ligament avulsion fracture - Hao Luo; Lin‐Feng Li; Song Han; Yu Pan; Fei‐Ju Xu; Tao Liu (Journal of Experimental Orthopaedics)
Abstract Purpose This study aims to describe a novel minimally invasive technique for the treatment of acute tibial posterior cruciate ligament (PCL) avulsion fracture. Methods This retrospective study included seven patients who underwent ultrasound‐guided fixation for acute PCL tibial avulsion fractures by using an adjustable‐loop device between January 2021 and January 2023. Before the surgery, the maximum diameter, area and displacement distance of the fragments were measured using computed tomography examination. All patients were followed up for at least 12 months, and clinical outcomes were assessed on the basis of range of motion, the International Knee Documentation Committee Score and the Lysholm score. Results For the seven patients, the mean maximum diameter, area and displacement distance of preoperative avulsion fragments were 12.7 mm (range, 9.0–48.3), 128 mm2 (range, 63–256.2) and 5.9 mm (range, 3.8–7.2), respectively. These fractures were fixed using an adjustable‐loop suspensory device under ultrasound guidance. Based on x‐ray examination during the post‐operative follow‐up period, all patients had no fracture displacement and fracture unions were confirmed, with a mean union time of 10.28 ± 2.13 weeks (range, 8–14). Based on the knee function assessment at 12‐month post‐operative follow‐up visit, all patients demonstrated excellent clinical outcomes. Conclusions Ultrasound‐assisted internal fixation using an adjustable‐loop device demonstrated satisfactory clinical and radiographic results. This technique has the advantages of being minimally invasive, safe, stable, convenient to operate and thus could be considered as a feasible alternative for the treatment of acute tibial PCL avulsion fractures. Level of Evidence Level III.